PENGARUH KOMPETENSI, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT MBK WILAYAH BANDUNG - Rinawati, Nenny (Majalah Bisnis & IPTEK, 2016)
This study aimed to determine the effect of competence, compensation and motivation on employee performance either partially or simultaneously. The object of research is a company engaged in the field of financial services. Survey research methods by inferential testing techniques by using path. Sampling technique with stratifield random of 127 employees, with a precision level of 5% in the sample can be as many as 107 employees. The results showed that there is significant influence of competency, compensation and motivation on employee performance either partially or simultaneously. Competence has contributed 22.81%, while compensation has contributed the most low at 21,35%, while the working motivation has the highest contribution of 22.98%, thus the simultaneous effect of competence, compensation and motivation of the employee performance by 67.14%. These results indicate that the effect of these three variables significantly, while the remaining 32.86% is determined by other variables. Keywords: competence; compensation; motivation; employee performance.